Domain theory and method theory in management accounting research - Kari Lukka; Eija Vinnari (Emerald Group Publishing Ltd., 2022)
Purpose
– The purpose of this paper is to distinguish two roles of theories, domain theory and method theory, and examine their relationships in management accounting research. Are these two roles explicitly distinguished in management accounting studies? Can this be achieved in an unambiguous manner? Where do ambitions for theoretical contribution lie in management accounting studies that employ method theories?
Design/methodology/approach
– The authors develop a conceptual framework for analysing possible relationships between domain theories and method theories in studies and illustrate the theoretical arguments with examples from management accounting studies employing Actor-Network Theory (ANT) as their method theory.
Findings
– There can be various types of relationships between domain theories and method theories, and the theoretical ambition of the analysed studies typically focused on domain theories. However, ambiguity can exist with regard to the location of a study's theoretical ambition. Both domain theories and method theories tend to be moving fields, and their interaction can add to this feature.
Research limitations/implications
– The suggested conceptual clarification assists in the reconciliation of extreme perspectives that relate to management accounting and theory. It will also help researchers to systematically design their own work and evaluate that of others. An increased understanding of how a field develops as a result of interaction with method theories might perhaps alleviate concerns regarding the value of mobilizing the latter.
Originality/value
– The analysis contributes to the on-going debate on the value and effects of employing method theories, or theoretical lenses, in management accounting research.